2002
DOI: 10.1021/ja011856m
|View full text |Cite
|
Sign up to set email alerts
|

Calix[4]tubes:  A New Class of Potassium-Selective Ionophore

Abstract: A new class of cryptand-like ionophore based on a bis calix[4]arene structure has been developed. These molecules proved highly selective for complexation of potassium over all group I metal cations and barium. A range of symmetric and asymmetric calix[4]tubes featuring either alkyl or phenyl substituents at the upper rim have been synthesized in exceptional yield. Alteration of the calix[4]arene upper rim environment enables fine-tuning of the rate of potassium uptake, which can be evaluated through the confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
81
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 35 publications
(47 reference statements)
6
81
0
1
Order By: Relevance
“…We recently demonstrated that fluorescently labeled calix [4]arene have the potential to track progress of the macrocycle in cells, as an NBD labeled cationic derivative was readily and speedily taken up into cells and provided a very stable, nontoxic read-out system to investigate cellular localization (20). The absorbance and emission spectra for the NBDCalAm showed that it can easily be visualized using a GFP filter (20).…”
Section: Key Termsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that fluorescently labeled calix [4]arene have the potential to track progress of the macrocycle in cells, as an NBD labeled cationic derivative was readily and speedily taken up into cells and provided a very stable, nontoxic read-out system to investigate cellular localization (20). The absorbance and emission spectra for the NBDCalAm showed that it can easily be visualized using a GFP filter (20).…”
Section: Key Termsmentioning
confidence: 99%
“…
AbstractThe uptake of a fluorescently labeled cationic calix [4] (NBDCalAm) in live, nonfixed cells has been investigated. The compound is taken into the cells rapidly and shows distinct endosomal distribution after 2 hours.
…”
mentioning
confidence: 99%
See 3 more Smart Citations